Electrochemical preparation and characteristics of platinum electrode surfaces with preferred orientations - Cerviño, R. M. (1985)
A new electrochemical procedure to obtain platinum electrode surfaces with preferred orientations from bulk polycrystalline platinum is presented. The procedure involves the application of repetitive potential sweeps at high frequencies to a polycrystalline platinum electrode under carefully selected potential perturbation conditions. The electrochemical response of the surface structures achieved after the treatment approach closely those reported in the literature for determined types of platinum single crystal faces.